Trigger warning [compact disc, unabridged] : short fictions and disturbances - Gaiman, Neil (Harper Audio, 2015)
A rich cornucopia of horror and ghosts stories, science fiction and fairy tales, fabulism and poetry that explore the realm of experience and emotion.